PENGARUH TARIF DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT Tk. II dr. AK. Gani Palembang: PENGARUH TARIF DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT Tk. II dr. AK. Gani Palembang - M. Hasan Azhari. Yulita Eka Fitri (STIKES Hesti Wira Sriwijaya, 2023)
ABSTRACTThere was a decrease in the number of inpatients allegedly caused by the increase in service rates at the Tk II Dr. AK Gani Hospital, Palembang. Apart from the problem of increasing retribution rates for health services, it is also due to the weakening performance indicators of Dr. AK Gani Palembang Hospital. Service providers who set prices according to the quality of their services can create customer satisfaction so that it will increase the company's good name. So it is felt necessary to do research on